Isolation, screening and characterization of riboflavin producing lactic acid bacteria from Katpadi, Vellore district - Jayaraman and Gurumurthy Kalaichelvan, Sathyanarayanan Jayashree, Kunthala (Recent Research in Science and Technology, 2010)
Riboflavin is a basic component of the cellular metabolism since it is the precursor of the coenzymes flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD). Riboflavin producing lactic acid bacteria are of potential importance to the fermented food industry since the chemical processes is being replaced by the fermentative biotechnological methods. The present study was carried out to identify and characterize the best riboflavin producing lactic acid bacteria from the yoghurt samples of the Vellore district. The strains isolated belong to the genus Lactobacillus, streptococcus, Pediococcus, and Leuconostoc. Lactobacillus was the predominant strain. The best riboflavin producing strain was characterized to be Lactobacillus fermentum by both biochemical as well as molecular methods from the Institute of microbial technology (IMTECH), Chandigarh, India and deposited with the accession number MTCC 8711. The strain could be a better starter replacing the conventional lactic acid bacteria where in the fermented foods could be naturally fortified with the riboflavin.